2011
DOI: 10.1108/14684521111113623
|View full text |Cite
|
Sign up to set email alerts
|

Understanding knowledge sharing in virtual communities

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 56 publications
(93 reference statements)
6
30
0
2
Order By: Relevance
“…Although past literature has verified many influential factors on knowledge-sharing, there are still disputes over several factors. For example, the effect of trust on knowledge sharing is disputed [48,49]. Some researchers find that social trust has no significant effect on employees' intention in sharing knowledge.…”
Section: Knowledge-sharingmentioning
confidence: 99%
“…Although past literature has verified many influential factors on knowledge-sharing, there are still disputes over several factors. For example, the effect of trust on knowledge sharing is disputed [48,49]. Some researchers find that social trust has no significant effect on employees' intention in sharing knowledge.…”
Section: Knowledge-sharingmentioning
confidence: 99%
“…An often-used measure of knowledge sharing is to investigate the frequency of sharing over a given period of timefor example, 'daily', 'once a week', or 'once a month' (Razmerita et al, 2016). Other studies have mapped general willingness to share knowledge with others (Chiu et al, 2011;Fehrenbacher & Wiener, 2019).…”
Section: Knowledge Sharing In Idea Conversationsmentioning
confidence: 99%
“…Researches conducted on equity theory (Thau & Mitchell, 2010;Chiu, Wang, Shih, & Fan, 2011) have demonstrated that perceived justice impacts human behavior especially in case of employees. However, Khanmohammadi (2014) believes that perceived justice can impact relationship between trust, individual attitude, and management support and reward system with knowledge sharing among university lecturers.…”
Section: Justice and Knowledge Sharingmentioning
confidence: 99%